When theory meets practice: applying cambourne’s conditions for learning to professional development for elementary school efl teachers (2011)
This article presents a reflection on an action research project carried out by a group of teachers and students at Universidad de Antioquia. The action research project aimed at etermining the impact of a professional development proposal for elementary school English teachers in Medellin, Colombia. In the first section, the article describes the previous study that supported this project as well as its design and implementation. In the second part, Cambourne’s conditions for learning are discussed from a theoretical and practical perspective. Researchers found that participant teachers improved both their use of the foreign language and their pedagogical practices as a result of having the opportunity to take risks and reflect as learners and teachers on holistic strategies for teaching and learning English as a foreign language.Este artículo presenta una reflexión acerca de un proyecto de investigación llevado a cabo por un grupo de profesoras y estudiantes de la Universidad de Antioquia. Este proyecto de investigación acción tuvo como objetivo principal determinar el impacto de una propuesta holística de desarrollo profesional para maestros de inglés de la básica primaria, en Medellín, Colombia. En la primera sección del artículo se describen el diseño y la implementación del proyecto así como el estudio anterior que dio origen al presente proyecto. En la segunda parte se discuten las condiciones para el aprendizaje y propuestas por Cambourne, desde una mirada teórica y práctica. Se encontró que los profesores participantes mejoraron en su uso de la lengua extranjera, así como en sus prácticas pedagógicas, como resultado de la toma de riesgos y la reflexión como aprendices y docentes acerca de estrategias holísticas para la enseñanza y el aprendizaje del inglés como lengua extranjera.